2017
DOI: 10.3201/eid2301.160817
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis Associated with Simultaneous Infection by Multiple Dengue Virus Serotypes in Children, Brazil

Abstract: To determine the causes of viral meningitis, we analyzed 22 cerebrospinal fluid samples collected during the 2014–2015 dengue epidemics in Brazil. We identified 3 serotypes of dengue virus (DENV-1, -2, and -3), as well as co-infection with 2 or 3 serotypes. We also detected the Asian II genotype of DENV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
2
21
1
Order By: Relevance
“…Araujo et al 24 found that 3.8% (8/209) of CSF tested positive for dengue in a study of 183 patients with suspected viral meningitis/meningoencephalitis and 26 deceased patients with suspected meningitis 24 . Marinho et al 25 detected DENV-1, -2, and -3 co-infections in 31.8% (7/22) of CSF of paediatric patients having viral meningitis 24 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Araujo et al 24 found that 3.8% (8/209) of CSF tested positive for dengue in a study of 183 patients with suspected viral meningitis/meningoencephalitis and 26 deceased patients with suspected meningitis 24 . Marinho et al 25 detected DENV-1, -2, and -3 co-infections in 31.8% (7/22) of CSF of paediatric patients having viral meningitis 24 25 .…”
Section: Discussionmentioning
confidence: 99%
“…An NGC-like strain detected in Jamaica in 2007, causing mild dengue disease, was also grouped within the Asian II genotype 8 . Interestingly, the Asian II genotype caused meningitis in patients from Minas Gerais, in the southeast region of Brazil 9 , within the same timeframe as our sample collection. Our results confirmed Asian II genotype of DENV-2 circulation in Brazil, in addition to the prevalent Asian/American genotype.…”
mentioning
confidence: 65%
“…It highlights the potential of the DEN-IM workflow to accurately detect and recover multiple DENV genomes from samples with DENV co-infection, even if the serotypes are present in low abundance. Indeed, recent studies from areas of high endemicity suggest that co-infection with multiple DENV serotypes may frequently occur [26] [27] and the co-circulation of different DENV strains of the same serotype, but distinct genotypes, in these areas [26] raises the possibility of simultaneous infection with more than one genotype.…”
Section: Discussionmentioning
confidence: 99%